2021
DOI: 10.1155/2021/9388562
|View full text |Cite|
|
Sign up to set email alerts
|

Investigating the Effects of Dapagliflozin on Cardiac Function, Inflammatory Response, and Cardiovascular Outcome in Patients with STEMI Complicated with T2DM after PCI

Abstract: Objective. To explore the effect of dapagliflozin on cardiac function, inflammation, and cardiovascular outcome in patients with ST-segment elevation myocardial infarction (STEMI) combined with type 2 diabetes (T2DM) after percutaneous coronary intervention (PCI). Methods. 70 patients with STEMI and T2DM were divided into the control group (n = 35) and the observation group (n = 35). Before surgery, patients in both groups were given conventional treatments such as coronary expansion, antiplatelet, anticoagula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…When combined with existing guideline-directed medical therapy, sodium-glucose cotransporter 2 (SGLT2) inhibitor dapagliflozin has been shown to minimize hospitalization for heart failure or mortality linked with cardiovascular causes in recent randomized controlled trials, including DAPA-HF [82][83][84]. According to one study, dapagliflozin treatment for patients with ST-segment elevation myocardial infarction (STEMI) and type 2 diabetes mellitus after percutaneous coronary intervention (PCI) can improve cardiac function, reduce inflammation, and lower the risk of adverse cardiovascular outcomes [85]. Metformin and dapagliflozin both decreased doxorubicin-induced myocardial damage in our investigation, possibly through the mechanisms outlined above.…”
Section: Discussionmentioning
confidence: 99%
“…When combined with existing guideline-directed medical therapy, sodium-glucose cotransporter 2 (SGLT2) inhibitor dapagliflozin has been shown to minimize hospitalization for heart failure or mortality linked with cardiovascular causes in recent randomized controlled trials, including DAPA-HF [82][83][84]. According to one study, dapagliflozin treatment for patients with ST-segment elevation myocardial infarction (STEMI) and type 2 diabetes mellitus after percutaneous coronary intervention (PCI) can improve cardiac function, reduce inflammation, and lower the risk of adverse cardiovascular outcomes [85]. Metformin and dapagliflozin both decreased doxorubicin-induced myocardial damage in our investigation, possibly through the mechanisms outlined above.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in LVIDD over time may indicate decongestion and/or reverse remodelling in response to HF treatment. Studies have shown a reduction of LVIDD in response to treatment with sacubitril/valsartan, dapagliflozin, eplerenone, or valsartan for up to 22 months [27][28][29][30][31]. Given the differences in LVIDD reduction in DCM versus ICM, it is possible that current optimal medical therapy produces more favourable ventricular remodelling in DCM patients.…”
Section: Discussionmentioning
confidence: 99%
“…MI is characterized by myocardial damage and apoptosis. MI triggers neuroendocrine regulations and an inflammatory response, resulting in changes in the morphological structure of the myocardium, ultimately affecting diastolic and systolic function ( 24 , 25 ). Wilcox et al determined that patients who suffered from MI were far less likely to experience HFiEF at 2 years ( 26 ).…”
Section: Discussionmentioning
confidence: 99%